Revitalizing Government Functions in Village Planning: A Multisite Study Based on Deconcentration and Decentralization Theory in Kendalbulur and Bendungan Villages - Nahadhiyanto, Ahmadi Abdul Shomad Faiz; Nur, Iffatin; Aziz, Abdul (IKIP Widya Darma Surabaya, 2025)
Objective: This study aims to analyze the revitalization of government functions in the formulation of village regulations based on the theoretical framework of deconcentration and decentralization, with a multisite focus on Kendalbulur and Bendungan Villages, Indonesia. The research seeks to address the following questions:1. How do the authority and capacity of village governments influence the formulation of village regulations? 2. How is the involvement of public consultants integrated into the regulatory drafting process? 3. How is community participation manifested in the formulation of village regulations? 4. How do village regulations reflect the realization of good governance? Method: This study employs a qualitative approach with a multisite case study design, using in-depth interviews, participatory observations, and document analysis to explore the dynamics of village governance. Results: The findings show that the authority and administrative capacity of village governments play a crucial role in fostering good governance. The integration of deconcentration and decentralization theories, complemented by the moral perspective of Siyasyah Dusturiyyah, emphasizes the importance of ethical considerations in every stage of policy-making. The involvement of public consultants, although still limited by budgetary and administrative constraints, has proven effective in enhancing the technical quality, accountability, and transparency of village regulation drafting. Community participation remains largely symbolic, with limited impact on the substance of policy. Novelty: This research offers novelty by integrating the perspectives of deconcentration, decentralization, and Islamic ethics of Siyasyah Dusturiyyah into the theoretical model of